Chemical composition and antimicrobial activity of essential oils in Xerophytic plant Cotula cinerea Del (Asteraceae) during two stages of development: flowering and fruiting - Chouikh Atef, Mayache Boualem, Maazi Mohamed Cherif, Hadef Youcef, Chefrour Azzedine (Journal of Applied Pharmaceutical Science, 2015)
The essential oil (EO) of Cotula cinerea Del collected in the region of Oued Souf (South-eastern Algeria) during two stages (flowering and fruiting), gave a performance that are 0.0801% ± 0.0117% at the flowering stage; and 0.391% ± 0.0664% at the fruiting stage. The chemical study of the (EO) of C. cinerea Del, analyzed by GCMS, showed the presence of 22 chemical compounds in the flowering period with the dominance of: 3-Carène (30.99%), Thujone (21.73%), Santolina triene (18.58%) and Camphor (6.21%). While 21 chemical compounds were obtained during the fruiting period with the dominance: Thujone (28.78%), 3-Carène (15.90%), Eucalyptol (15.13%), Santolina triene (13.38%) and Camphor (7.49%).Viewpoint chemical kinetics and composition, it was noticed that during the flowering stage the plant has produced eight compounds that are absent during the fruiting period. While seven other compounds appeared only during fruiting. It appears the antibacterial of (EO) has C. cinerea Del The sensitivity of the bacterial strains tested; and E. faecium, E.coli, M. morganii, P. vulgaris, S. aureus and A. baumannii has shown great sensitivity; the strain P. aeruginosa have shown stiff resistance with every concentrations of (EO). As we did not notice any differences significant in the diameters of inhibition with all strains in two stages of growth.
Keywords: Cotula cinerea Del, Essential oil (EO), GCMS, Antibacterial, Flowering,Fruiting.